Construction of Si3N4/SiO2/SiC–Y2Si2O7 composite ceramics with gradual impedance matching structure for high-temperature electromagnetic wave absorption. Issue 16 (15th August 2022) - Wei, Hanjun; Yang, Shenquan; Feng, Pei; Xue, Jimei; Zhao, Feng; Wang, Qingyuan
Abstract: Good impedance matching is vital in upgrading the performance of electromagnetic (EM) wave-absorbing materials. In this study, Si3 N4 /SiO2 /SiC–Y2 Si2 O7 composite ceramics were synthesized by sintering and chemical vapor infiltration (CVI) technology with gradual impedance matching. The relationship between the microstructure of the as-prepared composite ceramics and EM wave absorption characteristics was thoroughly explored. It was found that the amorphous Si3 N4, SiO2, and SiC layers were constructed with a gradual impedance matching structure, which not only improved impedance matching but also increased the number of nano interfaces. More importantly, SiC nanocrystals effectively increased the conduction loss, and the presence of defects and nanoscale heterogeneous interfaces further increased the polarization loss. Consequently, the as-prepared composite ceramics displayed enhanced EM wave absorption properties, with a minimum reflection coefficient (RCmin ) value of less than −20 dB over a temperature range of 25 °C (RT)-300 °C, and an effective absorption bandwidth (EAB) maintained at 4.2 GHz with the thickness range of 3.75–4.75 mm. These results demonstrated the practical significance of high-performance EM wave absorption materials that can be applied in high-temperature and water vapor environments.